São Paulo’s Girls: image of a dressed body by fashion (ModaPalavra e-periódico, 2008)
The paper focus some ideas to will be articulated hereafter a determined body had reproduced by the hands of the Brazilian fashion designer Alceu Penna, in the section of column As Garotas of the Brazilian magazine O Cruzeiro in the age of 1953. The intention is to introduce the notion of body and his relations and inter-relations about anothers concepts that will be articulate in go of the text like the idea of feminine´s body, translated in a dressed body by the fashion and also how this body is been socialized and transmitted until to the reader public of visuals and writings texts. So, refer another concept that has relation with the surroundings, the space here represented by São Paulo City, been aimed some traditionals neighbourhoods. These correlations share our biggest preoccupation how are establishing and determined feminine´s body in these visual text represented by image in the question that entitle “As Garotas de S. Paulo”.
Keywords: body; city; fashion